Evaluating Inpatient Daily Census Completeness for Bed Uti-lization Efficiency at Assyifa Hospital Sukabumi Using the 5M Framework - Ai Septiani Al Fitri; Musta’inul Habibi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aims to evaluate the completeness of inpatient daily census data and its impact on bed utilization efficiency at Assyifa Hospital Sukabumi using the 5M framework (Man, Machine, Method, Material, Money). Accurate inpatient census recording is essential for effective hospital management, particularly in optimizing bed occupancy rates and ensuring efficient resource allocation. However, issues related to incomplete data entry often lead to inaccuracies in bed utilization monitoring. By applying a qualitative descriptive approach, this research explores various factors influencing census completeness and their implications for bed usage. Data were collected through interviews, observations, and documentation, involving 37 nurses responsible for census recording. The findings reveal that human factors such as workload and understanding of standard operating procedures, technological limitations, procedural inconsistencies, inadequate supporting materials, and insufficient financial support are significant contributors to census incompleteness. Recommendations include enhancing staff training, improving technological systems, clarifying standard procedures, ensuring adequate materials, and allocating sufficient funding. This study provides valuable insights for hospitals aiming to improve their data recording processes and optimize resource utilization effectively.